Dentists Ergonomic Knowledge and Attitudes in North-Est Region, Romania - Lucia Bârlean; Ioan Dănilă; Iulia Săveanu (Romanian Society of Oral Rehabilitation, 2012)
The ergonomic education of the dental health-care personnel must focus on the considerable occupational health risks. Aim. The aim of this study was to assess the dentists' knowledge and attitudes towards ergonomics during dental health-care. Methods A questionnaire-based study was conducted including 152 dentists (72,4%-females, 27,6%-males) aged between 25-65 years, from North-Est Region, Romania. The questionnaire included 13 questions related to ergonomic practices in the dental office. Data were statistically analysed using the SPSS 14.0 program and chi-square test